Working Memory Training Improves Emotion Regulation Ability. Issue 1 (December 2018) - Xiu, Lichao; Wu, Jie; Chang, Lei; Zhou, Renlai
Abstract Emotion regulation deficits are associated with various emotional disorders. Therefore, studies have attempted to improve emotion regulation ability to prevent psychopathological symptoms. Studies have revealed that working memory training—specifically attention control—can promote emotion regulation. In the present study, participants completed a running memory task in a 20-day training period. The participants' pre- and post-test data on attention network functions and late positive potential (LPP) were assessed and analyzed. Compared with the control group, the training group's orientation function improved markedly. In addition, LPP in relation to emotion regulation decreased during the 20-day training period. These results suggest that working memory training can improve emotion regulation ability, and the orientation function in the attention network may also contribute to this improvement.